Transplante renal e risco de câncer de cabeça e pescoço : revisão sistemática e meta-análise - Martins Filho, Paulo Ricardo Saquete (2014)
Kidney transplantation and head and neck cancer risk: systematic review and meta-analysis Paulo Ricardo Saquete Martins Filho, Aracaju/SE, Brazil, 2013. Background: Kidney transplantation is considered the treatment of choice for end-stage kidney disease, but a wide-ranging excess risk of post-transplant malignancies has been recognized as a complication of long-term immunosuppression. De novo malignancies are important cause of morbidity and mortality in kidney recipients. We performed a systematic review and meta-analysis to determine the risk of head and neck cancer after kidney transplantation. Methods: A systematic search was performed in PUBMED, EMBASE, SCOPUS, and LILACS databases to identify cohort studies reporting on the risk of head and neck cancer in kidney recipients. The assessment of validity of selected studies was performed using the STROBE statement and the Newcastle-Ottawa Scale (NOS) for Cohort Studies. Only studies with NOS ≥ 6 were included in the meta-analysis. Pooled relative risks (RR) were calculated using the Mantel-Haenszel or DerSimonian-Laird method, depending on statistical heterogeneity. To detect publication bias, Egger‟s test, Duval and Tweedie‟s analysis, and leave-one-out sensitivity analysis were conducted. Results: A total of 9 high-quality cohort studies were included in the meta-analysis. The pooled RR of head and neck cancer after kidney transplantation was 8.2 (95% CI 4.0-16.6, p<0.0001). A significant excess risk of cancer was observed in the lip (RR = 43.6, 95% CI 24.2-78.4, p<0.0001). The pooled RR of oral cavity/pharynx and salivary gland was 3.5 (95% CI 2.5-5.0, p<0.0001) and 5.6 (95% CI 1.3-24.0, p = 0.020), respectively. No evidence of publication bias was observed. Conclusion: There is an increased risk of head and neck cancer after kidney transplantation. The head and neck should be examined routinely during the post-transplant surveillance.